PERSETUJUAN BANGUNAN GEDUNG SEBAGAI BAGIAN DARI PERIZINAN PEMBANGUNAN PERUMAHAN OLEH PT KRIYA NUSWANTARA GEMILANG DI KABUPATEN KARAWANG - Melliana; Farhan Asyhadi; Muhammad abas (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The Building Approval (Persetujuan Bangunan Gedung or PBG) is a form of government-issued authorization required for any individual or legal entity intending to undertake construction, expansion, modification, or demolition of a building. The Building Approval (PBG) came into effect following the government’s replacement of the Building Construction Permit (IMB) system through Law Number 11 of 2020 on Job Creation and Government Regulation Number 16 of 2021. This study aims to examine the legal framework governing PBG and its implementation in residential development by PT Kriya Nuswantara Gemilang in Karawang Regency. The research employs a juridical-empirical approach, which combines the analysis of applicable legal norms with field data obtained through interviews. The findings indicate that, despite the comprehensive nature of the existing legal provisions on PBG, various challenges persist in practice. One such issue is the delay in permit issuance due to technical problems in the SIMBG (Online Building Approval System), coupled with insufficient dissemination of information by local government authorities. The case of PT KNG constructing a model house without formal authorization in early 2023 illustrates the suboptimal enforcement of the regulations. This study provides a concrete depiction of field-level problems and underscores the necessity of system improvements and enhanced inter-agency coordination to ensure a more orderly permit process that supports a secure investment climate.